A death in the family: a community's embodiment of tragedy. Issue 4 (8th August 2018) - Harmon, Justin
ABSTRACT: This manuscript explores how a tightknit music fan community responds to the suicide of one of its members. During the grieving process the music and music scene of the band Rust Forever are relied on for catharsis and healing, and the memories and legacy of the deceased are kept alive through the community's long-established bonds and commitment to helping one another through hard times. While the power and potential of music has been explored in other areas of healing and life transitions, its use in responding to tragedy is an underdeveloped area of investigation. Because suicide has such a traumatic impact on surviving loved ones, the conflict and blame that often accompany it were also present in this instance. This manuscript highlights the importance of close friends and meaningful leisure, particularly music, in the healing process associated with suicide, but also the ambiguity, stigma, and complicated emotions that accompany it.